A critical analysis of the role of the Movement for Democratic Change (MDC) in the democratisation process in Zimbabwe from 2000 to 2016 - Mwonzora, Gift (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
The thesis provides a critical analysis of the role of the Movement for Democratic Change (MDC) in contributing to processes of democratisation in Zimbabwe from 2000 to 2016. The MDC was formed in 1999 and it became the most important opposition party to the ruling Zimbabwe African National Union-Patriotic Front (ZANU-PF) party in Zimbabwe since independence in 1980. During this period, though, the MDC also entered into a coalition government with ZANU-PF under the Government of National Unity (GNU) from 2009 to 2013. In characterising the Zimbabwean state as a semi-authoritarian regime with a defiant ruling party, the thesis identifies and examines the significant challenges faced by the MDC in seeking democratisation, including within the realms of electoral, constitutional and legislative change. At the same time, the MDC suffered from significant internal problems including major splits, with the original MDC becoming MDC-Tsvangirai (MDC-T) in 2005. In focusing on the MDC and democratisation over the entire course of the party's existence, the thesis is able to identify any important differences between the pre-GNU period, the GNU period and the post-GNU period. As well, it is able to consider the changing relationships between the MDC and the pro-democracy forces from which it first emerged, namely urban civil society and trade unions. The thesis concludes that the effectiveness of the MDC in bringing about democratisation has been highly uneven across the realms of electoral, constitutional and legislative change, and that any changes are necessarily tentative and subject to reversals given the ongoing semi-authoritarian regime in which the ruling ZANU-PF party has in effect fused with the state. Though there has been some evidence of democratic transition in Zimbabwe under the influence of the MDC (and MDC-T), more far-reaching democratic consolidation remains elusive. The fieldwork for the thesis is in large part based on a qualitative research methodology, involving key informant interviews, observations, primary documentation, and participation in political rallies and public lectures.
Keywords: Uncatalogued